LinkedIn marketing : an hour a day - Rosen, Viveka von (Serious skills., 2012)
A step-by-step guide for succeeding on the for ''business'' social media network LinkedIn Marketing: An Hour a Day helps you create, customize, and optimize a presence on LinkedIn, the world's largest social network for professionals. In this detailed, step-by-step book, LinkedIn expert Viveka von Rosen reveals how to use this powerful platform to ensure that you or your company get noticed by the right audience. Discover previously undocumented tips and tricks for community growth and management, including how to best use Groups, events, and other LinkedIn features and applications. Offers a.